Rapid qualification of fused filament fabrication thermoplastics for cryogenic applications - Louis Vaught; Eduardo Gonzalez; Jacob L. Meyer; Andreas A. Polycarpou (Polymer Testing, 2023)
Thermoplastic additive manufacturing (AM) is an attractive process for fabricating cryogenic componentry, due to the potential for rapid, on-site parts replacement. However, using a process intended for low-feature prototypes in such a demanding application creates survivability concerns. AM further introduces significant material variability that complicates materials qualification. Herein, a highly-repeatable test procedure is developed to qualify as-manufactured samples. Fused Filament Fabrication (FFF) is used to produce both test samples and custom immersion equipment for cryogenic tensile testing, and data quality is improved by modifying the ASTM Type IV geometry. Tensile strength is measured directly, while elastic modulus is calculated using temperature measurements and thermomechanical model fitting. Via this methodology, cryogenic performance is characterized for Polylactic Acid (PLA), Acrylonitrile Butadiene Styrene (ABS), and Glycol-Modified Polyethylene Terephthalate (PETG). PLA notably demonstrates acceptable strain to failure of 2.6 % and a favorable increase in strength from 47 to 120 MPa when cooled. Testing of carbon fiber filled PLA (CF-PLA) finds a remarkable 250 % increase in strength, from 37 to 130 MPa. Both materials withstand 10 high-stress thermal cycles with mild strength gain, causing a loss of room temperature ductility in neat PLA but not CF-PLA. Dynamic Mechanical Analysis (DMA) indicates a β-transition at −20 to −40 °C, which correlates with the observed changes. These findings show AM thermoplastics are promising for use in cryogenic laboratory environments, and could be modified for use in production applications.